O Pewnym Rozwiązaniu Płyty Trójwarstwowej - Ganowicz, R. (Engineering Transactions, 1966)
This paper is devoted to the solution of the problem of-a three-layer (sandwich) plate subjected to a concentrated force. This solution is confronted with the known singular solution for a thin plate. As regards of the three-layer (sandwich) plate under consideration it is assumed that its outer layers are isotropic and have no flexural rigidity and that the omiddle layer carries shear forces only.